Potential, Challenges and Prospects: Internationalization of Small and Medium Enterprises (SMEs) in Malang Raya - Herman Herman; Imam Mukhlis; Fulgentinus Danardana Murwani (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to investigate issues related to the phenomenon of internationalization of SMEs in Malang Raya, analyze the potential and challenges faced, and formulate future prospects. The method used in this research is qualitative phenomenology. The results of this research are that internationalization has become an important strategy for Small and Medium Enterprises (SMEs) in various parts of the world, including in Malang Raya. Malang Raya, with its rapidly growing economic potential and product diversity, offers great opportunities for SMEs to expand their market reach to an international level. However, to achieve success in internationalization, SMEs in Malang Raya are faced with various challenges, including capital issues, human resource management, technology and market access.